MEASUREMENT OF THE NATURAL VARIATION OF C-13 - C-12 RATIO IN LEAVES AT RESERVA DUCKE FOREST, CENTRAL AMAZONIA - Ducatti, C.; Salati, E.; Martins, D. (Elsevier B.V., 1991)
Investigation of carbon isotope fractionation by plants was carried out at two sub-areas located in Reserva Ducke, central Amazonia: open reserve (virgin forest with low density of plant species); and closed reserve (virgin forest with high density of plant species). Preliminary results (delta-parts per thousand C-13:C-12 values, PDB) of leaf analysis at different plant heights indicate the following: Eschweilera matamata Hub. (Lecythidaceae), common name 'matamata', -31.55 +/- 0.61; Protium heptaplyllum March. (Burseraceae), common name 'breu branco', -32.34 +/- 1.39; Calophyllum brasiliense Camb. (Guttiferae), common name 'jacareuba', -30.72 +/- 0.23; Scleronema micrantthum Ducke. (Bombacaceae), common name 'cardeiro'. -28.81 +/- 0.68; and Carapa guianensis Aubl. (Meliaceae), common name 'andiroba', -31.07 +/- 0.51.It is possible that the plant species analysed belong to the C3 photosynthetic cycle.In general, the species in the open reserve show differences of the order of 1.66 +/- 0.34 parts per thousand (greater in C-13) as compared with the same species in the closed reserve. The old leaves show differences in the relative isotopic enrichment (delta) of the order of 1 parts per thousand, being smaller in new leaves in both reserves.The probable occurrence of an isotopic gradient from the lower (2-5 m) to the upper part (15-20 m) of the plant, of the order of 1.3 parts per thousand, smaller in C-13, in species from the dense forest was noted. However, only two plants from each species were analysed during a two-year period, data obtained so far are still preliminary, and results should, therefore, be revised. Moreover, according to the literature, the natural carbon isotope fractionation by plants shows metabolic, physiological and environmental dependence.